Loneliness, sociability and depression in old age home elderly - Panwar, Pooja; Kumar, Rajesh; Belsiyal, Xavier (International Journal Of Community Medicine And Public Health, 2019)
Background: Increasing elderly population became a big concern to health professionals. Loneliness, lack of socialization and depression is quite frequently reported in elderly population. Lack of evidence on impact of socialization and loneliness on depression necessitate this survey. The current work focused on level of socialization, loneliness and depression among elderly residing in old age homes. Methods: The cross-sectional survey includes 100 purposively selected elderly from selected old age homes, Uttarakhand. Elderly were interviewed by using University of California, Los Angeles (UCLA) Loneliness scale, Geriatric depression scale (GDS) and Eysenck personality inventory (EPI) sociability subscale of extroversion. Appropriate statistics was applied to generate results. Results: Findings revealed a significant relationship of loneliness with depression (r=-0.740, p<0.01) and sociability (r=0.195, p<0.01). Similarly, sociability and depression were found dependent on each other (r=-0.354, p<0.01) in elderly. Conclusions: Elderly residing in old age homes need due attention and care to get rid of these silent psychological problems. Timely medical care and measures to improve socialization may help to anticipate mortality and morbidity and protect the vulnerable population.